2018
DOI: 10.1101/381806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rho-mediated gene transcription promotes BRAF inhibitor resistance in de-differentiated melanoma cells

Abstract: Over half of cutaneous melanoma tumors have BRAFV600E/K mutations. Acquired resistance to BRAF inhibitors (BRAFi) remains a major hurdle in attaining durable therapeutic responses. In this study we demonstrate that approximately 50-60% of melanoma cell lines with vemurafenib resistance acquired in vitro show activation of RhoA family GTPases. In BRAFi-resistant melanoma cell lines and tumors, activation of RhoA is correlated with decreased expression of melanocyte lineage genes. Using a machine learning approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Several studies have reported that alterations of RHOA mediate tumor invasion and drug resistance in cancer. Misek et al 18 . found that RHOA contributes to BRAF inhibitor resistance in Sox9High/Sox10Low melanoma cells by regulating activation of the RhoA family signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that alterations of RHOA mediate tumor invasion and drug resistance in cancer. Misek et al 18 . found that RHOA contributes to BRAF inhibitor resistance in Sox9High/Sox10Low melanoma cells by regulating activation of the RhoA family signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that alterations of RHOA mediate tumor invasion and drug resistance in cancer. Misek et al 18 found that RHOA contributes to BRAF inhibitor resistance in Sox9High/Sox10Low melanoma cells by regulating activation of the RhoA family signaling pathway. In addition, partner genes with high degrees in the SL network, such as NAE1 and TP53, also played an important role in the development and progression of cancer.…”
Section: Drug-response-related Genetic Interaction Network Shows Biological Characteristicsmentioning
confidence: 99%
“…Our recent findings indicated a role of the Rho/MRTF pathway in migration, invasion and metastasis of aggressive human cutaneous melanoma (20,34), as well as in the acquired resistance of BRAF mutant melanoma cells to BRAF inhibitors (34). Therefore, we hypothesized that the Rho/MRTF pathway might play a role in the intrinsic resistance of some of the NRAS mutant melanoma cells to trametinib-induced inhibition of cell viability.…”
Section: Mrtf Pathway Activation Correlates With Trametinib Resistancementioning
confidence: 97%